Short Course on Industrialiezd Building System (IBS) - Anon (University Malaysia Perlis (UniMAP), 2013)
Short Course on Industrialized Building System organized by Universiti Malaysia Perlis in collaboration with Proven IBS Training Centre (M) Sdn. Bhd., 7-9th November 2012 at Kompleks Pengajian Kejuruteraan Alam Sekitar, Kompleks Pusat Jejawi 3, Arau, Perlis.